Palomino Horses - Monahan, Erin 1977- (Mankato, Minn. : Pebble Books, 2009)
"A brief introduction to the characteristics, life cycle, and uses of the Palomino horse breed"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Palomino horse -- Juvenile literature